Evolution of maximum permissible doses of ionizing radiation and role of accident of 1993 at the Siberian Chemical Plant in irradiation of people - F. F. Tetenev; A. I. Ryzhov; Ya. V. Porovsky (Бюллетень сибирской медицины, 2008)
In April 2008, it was 15 years after the accident at the radiochemical line of the Siberian Chemical Plant (SCP). Changes in the ionizing radiation background due to the accident of 1993 and results of investigation of the radiation situation in the SCP coverage zone are described. The data on state of health in people leaving in the zone of radiation track of the accident are ge-neralized. The results of our investigation are presented.